The Effectiveness of Audio-Visual Learning Media in Improving Arabic Speaking, Listening, and Vocabulary Skills: Evidence from Indonesian Students - Muh. Fihris Khalik (Yayasan Adra Karima Hubbi, 2026)
Background. The increasing demands of global communication and the integration of technology in education have highlighted the importance of mastering foreign languages, including Arabic. However, many university students continue to demonstrate low proficiency in Arabic, particularly in speaking and listening skills. This issue is often associated with limited variation in instructional Purpose. This study aims to evaluate the effectiveness of audio-visual media as a tool for strengthening Arabic language competency, particularly in speaking, listening, and vocabulary mastery. Method. This research employed a quantitative quasi-experimental design involving two groups: an experimental group that utilized audio-visual media and a control group that applied conventional learning methods. Results. The findings revealed that students in the experimental group showed significant improvement in speaking, listening, and vocabulary skills compared to those in the control group. Statistical analysis confirmed a significant difference in the mean scores, indicating that the use of audio-visual media had a positive and measurable impact on enhancing Arabic language competency. Conclusion. The study concludes that audio-visual media is an effective and engaging learning strategy for improving Arabic language skills. Its implementation not only enhances students’ comprehension and participation but also supports their readiness to meet the challenges of modern, technology-driven learning environments.